SPATIOTEMPORAL ANALYSIS OF FOREST LOSS AND LAND USE DYNAMICS IN THE SANGKULIRANG–MANGKALIHAT KARST ECOSYSTEM IN EAST KALIMANTAN - Purnama, Syaiful Muflichin; Wahyuningsih, Noor; Wirabumi, Putu; Karondia, Loryena Ayu (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2025)
The Sangkulirang-Mangkalihat Karst region faces increasing pressure from human activities, particularly Forest Loss, land-use conversion, and industrial expansion, threatening its ecological functions including water storage, biodiversity habitat, and ecosystem services. This study analyzes land use and land cover (LULC) dynamics and Forest Loss patterns in Berau and East Kutai Regencies from 2001 to 2023 using multitemporal remote sensing with Landsat-8 and Sentinel-2 imagery. Land cover classification employed Random Forest algorithm, achieving 90% spatial accuracy. Results reveal complex Forest Loss trends, with highest forest loss in Berau Regency while East Kutai shows fluctuating dynamics. Vegetation recovery was detected, particularly increased high-density forest cover and decreased open land during 2019–2023. Despite regeneration signs, the karst landscape remains under significant pressure from overlapping mining and plantation concessions. The study emphasizes implementing spatial conservation strategies and strengthening karst protection policies, supported by long-term remote sensing monitoring and machine learning algorithms to sustain the ecosystem. Keywords: Karst Ecosystem, Remote sensing, Land Use Land Cover